The revenge of Seven - Lore, Pittacus (New York, NY Harper, an imprint of HarperCollinsPublishers, 2014)
The Garde, broken and divided, discover that the Mogadorians have commenced their ultimate invasion plans and will stop at nothing to thwart it
Includes excerpts from three I am Number Four: The lost files novellas : Return to paradise, Five's legacy, and Five's betrayal
1
NEW, LITERATURE
Keywords: Extraterrestrial beings -- Juvenile fiction; Extraterrestrial beings; Imaginary wars and battles -- Juvenile fiction; Insurgency -- Juvenile fiction; Psychokinesis -- Juvenile fiction; Traitors -- Juvenile fiction; Fiction; Juvenile works; Science fiction; Young adult fiction